Radial piston triboelectric nanogenerator-enhanced cellulose fiber air filter for self-powered particulate matter removal. (December 2020) - Mo, Jilong; Zhang, Chenyuan; Lu, Yanxu; Liu, Yanhua; Zhang, Ni; Wang, Shuangfei; Nie, Shuangxi
Abstract: In recent years, air pollution has detrimentally affected human health. Particulate matter (PMx) is a primary component of air pollution, and significant research effort has been devoted to developing feasible technologies for its removal. In this study, a radial piston triboelectric nanogenerator (RP-TENG) enhanced cellulose fiber air filter (CFAF) was developed to remove PMx from outdoor ambient air. This self-powered PMx removal system can not only convert rotating mechanical energy into electrical energy, but it can automatically remove polluted air from the outdoor environment. After charging, the removal efficiency of the CFAF was 83.78% for PM2.5 and 86.82% for PM10, which were 1.21 times and 1.27 times greater than those of the uncharged system, respectively. The self-powered PMx removal system can be installed on an object with rotating mechanical energy, such as the rotating shaft of a shared bicycle, and the wasted rotating mechanical energy would be used to fully purify the outdoor environment. Furthermore, this system is environmentally friendly due to its low level of carbon emissions. This work has numerous potential applications as it provides a new and sustainable strategy for applying self-powered, TENG-enhanced air filters for the removal of PMx from outdoor air. Graphical abstract: Image 1 Highlights: The removal efficiency of PM2.5 and PM10 after charging is increased by 1.21 times and 1.27 times, respectively. A radial piston TENG structure is proposed, which converts mechanical energy into electrical energy. The 8-unit radial piston mechanism enables TENG to have higher electrical performance and air pumping efficiency. The proposed self-powered PMX removal system can be used to remove the smog by self-powered.